A novel secondary code acquisition algorithm for the BDS‐3 B1C signal - Qiu, Tongsheng; Wang, Xianyi; du, Qifei; Sun, Yueqiang; Wang, Zhuoyan (IET radar, sonar & navigation, 2021)
The BDS‐3 recently started broadcasting a new civil B1C signal to provide open services for global users, which brings benefits to GNSS‐based applications. The BDS‐3 B1C signal modulates a long secondary code on the primary code in the pilot component, and it is useful to acquire the secondary code so as to extend coherent integration time when acquiring weak BDS‐3 B1C signals. However, the long secondary code of the BDS‐3 B1C signal puts FFT‐based and multi‐hypothesis‐based secondary code acquisition methods in trouble from the high computational burden. Therefore, the authors propose a novel secondary code acquisition algorithm called the partial correlation method (PCM) for the BDS‐3 B1C signal. The PCM acquires the secondary code in three steps to reduce the complexity and acquisition time, and it supports up to 110ms coherent integration and can be applied for the case of C/N0≥25dB‐Hz, which satisfies most cases. Further, a matched‐filter‐based architecture of the PCM is presented. Additionally, the characteristic length vector to determine the secondary code chip position quickly is proposed, which is better than the existing characteristic length method. Finally, experimental results based on real BDS‐3 B1C signals data show that the proposed PCM is effective.